(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The article is devoted to the study of the phenomenon of pleonasm in the Russian language, its history and modern approaches to its analysis. The article considers the evolution of the concept of "pleonasm" from ancient rhetorical treatises to modern linguistic studies. The article analyzes the attitude to pleonasm in Russian rhetorics of the XVIII century, works of linguists of the XIX century (F. I. Buslaev, A. A. Potebni), as well as in modern lexicographic and encyclopedic sources. The author identifies the main types of pleonasm (accumulation of synonyms, paired naming, redundant words) and considers the criteria for its normativity. Special attention is paid to the correlation between pleonasm and tautology, as well as its stylistic and pragmatic functions in modern Russian.